Analysis of Current Ratio and Debt To Asset Against Changes in Profit of Pharmaceuticals Companies - Dian Efriyenty (Owner : Riset dan Jurnal Akuntansi, 2021)
PT Kalbe Farma Tbk. experienced a slowdown in growth to reach 14.7%. In 2016-2017 the stage increase was only 7.3 %%. PT Kimia Farma Tbk. feel the same state. In 2016-2017 the increase in income reached 22.90%. The number of pharmaceutical companies experiencing changes in profit is quite rapid. News is now developing in various countries. The rise and fall of profits in the economic conditions of the pharmaceutical business. The purpose of this research is to see whether liquidity, solvency, and profitability have an individual and simultaneous influence on changes in earnings in Pharmaceuticals entities that are visible on the Indonesia Stock Exchange. Financial ratio analysis is used as a measurement of management's ability to earn a predetermined profit in management performance and utilize company resources effectively. The method of observation is descriptive research, with a population that states ten pharmaceutical industries located on the Indonesia Stock Exchange and 45 samples from 9 pharmaceutical companies were determined. Methods of data analysis used regression before the classical assumption test. The partial test results prove that the current ratio and debt to assets have an impact on changes in earnings. Current and joint long-term debt has no impact on changes in earnings.